Lingguizhugan oral solution alleviates MASLD by regulating bile acids metabolism and the gut microbiota through activating FXR/TGR5 signaling pathways - Wang, Jiahua; Zang, Juan; Yu, Yang; Liu, Yang; Cao, Huimin; Guo, Ruibo; Zhang, Lu; Liu, Mo; Zhang, Zixu; Li, Xuetao; Kong, Liang (Frontiers in Pharmacology, 2024)
The preservation of the Lingguizhugan (LGZG) decoction and patient compliance issue often limit the treatment of metabolic dysfunction-associated steatotic liver disease (MASLD). Hence, herein, an LGZG oral solution was developed for alleviating MASLD. Additionally, the potential mechanisms underlyingLGZG-mediated MASLD mitigation were explored.Methods: A MASLD mouse model was constructed using oleic and palmitic acid-induced LO2 cells and a high-fat diet. The apoptosis, lipid deposition, and mouse liver function were analyzed to assess the therapeutic effects of the LGZG oral solution on MASLD. Serum untargeted metabolomics, gut microbiota, bile acid (BA) metabolism, immunohistochemistry, and western blotting analyses were performed to investigate the potential mechanism of action of LGZG oral solution on MASLD.The LGZG oral solution ameliorated lipid deposition, oxidative stress, inflammation, and pathological damage. Serum untargeted metabolomics results revealed the LGZG-mediated regulation of the primary BA biosynthetic pathway. The 16S ribosomal RNA sequencing of the fecal microbiota showed that LGZG oral solution increased the relative abundance of the BA metabolism-associated Bacteroides, Akkermansia, and decreased that of Lactobacillus. Additionally, the BA metabolism analysis results revealed a decrease in the total taurine-α/β-muricholic acid levels, whereas those of deoxycholic acid were increased, which activated specific receptors in the liver and ileum, including farnesoid X receptor (FXR) and takeda G protein-coupled receptor 5 (TGR5). Activation of FXR resulted in an increase in short heterodimer partner and subsequent inhibition of cholesterol 7α-hydroxylase and sterol regulatory element-binding protein-1c expression, and activation of FXR also results in the up-regulation of fibroblast growth factor 15/19 expression, and consequently inhibition of cholesterol 7α-hydroxylase, which correlated with hepatic BA synthesis and lipogenesis, ultimately attenuating lipid deposition and bile acid stasis, thereby improving MASLD.Altogether, the findings of this study suggest that modulating microbiota-BA-FXR/TGR5 signaling pathway may be a potential mechanism of action of LGZG oral solution for the treatment of MASLD.